A Campanha de Aperfeiçoamento e Difusão do Ensino Secundário (CADES): contribuições para a Educação Matemática - Santana, Rogério Joaquim (2021)
This work deals with the contributions to Mathematics Education from the materials (articles, books, proposals and methods) of the Campaign for the Improvement and Dissemination of Secondary Education (CADES), an initiative promoted by the Ministry of Education and Culture and which ran from 1953 to 1971 in Brazil. The investigation took place based on a qualitative approach, through descriptions and interpretations, and also aimed to carry out a critical analysis of the materials produced by CADES that are directly related to Mathematics Education, indicating the correlations found with the materials and recommendations produced in second decade of the 21st century, mainly the Common National Curriculum Base (BNCC) and the Common National Base for Initial Teacher Training in Basic Education (BNCTraining). The work provides a brief description of the contextual conditions for the production of CADES materials, in addition to exploring in greater depth the texts and activities recommended by the campaign, with special attention to directed study, a teaching method aimed at encouraging the autonomy of students. The analyzes take place throughout the work and have, as theoretical contributions, the theories of French didactics, especially the Theory of Didactic Situations (TSD)